Harmful Practices and the Universality of Morality (KULT_online, 2012)
Janne Mende's anthropological-philosophical treatise on universalism and cultural relativism uses the example of female genital mutilation, depicting the rationales of the practice, which affects more than 130 million girls and women worldwide, its medical risks and its status as a human rights violation. Furthermore, the book introduces the reader – convincingly, with the exception of a subchapter on the health perspective – to a feminist and post-colonially framed discourse that entails several controversies as well as a philosophical debate on the universality of morality, which has extensive practical consequences.